Effect of emergent carotid stenting during endovascular therapy for acute anterior circulation stroke patients with tandem occlusion: A multicenter, randomized, clinical trial (TITAN) protocol. Issue 3 (April 2021) - Zhu, François; Hossu, Gabriela; Soudant, Marc; Richard, Sébastien; Achit, Hamza; Beguinet, Mélanie; Costalat, Vincent; Arquizan, Caroline; Consoli, Arturo; Lapergue, Bertrand; Rouchaud, Aymeric; Macian-Montoro, Francisco; et al.
Background and hypothesis: There is no consensus on the optimal endovascular management of the extracranial internal carotid artery steno-occlusive lesion in patients with acute ischemic stroke due to tandem occlusion. We hypothesized that intracranial mechanical thrombectomy plus emergent internal carotid artery stenting (and at least one antiplatelet therapy) is superior to intracranial mechanical thrombectomy alone in patients with acute tandem occlusion. Study design: TITAN is an investigator-initiated, multicenter, prospective, randomized, open-label, blinded-endpoint (PROBE) study. Eligibility requires a diagnosis of acute ischemic stroke, pre-stroke modified Rankin Scale (mRS)≤2 (no upper age limit), National Institutes of Health Stroke Scale (NIHSS)≥6, Alberta Stroke Program Early Computed Tomography Score (ASPECTS)≥6, and tandem occlusion on the initial catheter angiogram. Tandem occlusion is defined as large vessel occlusion (intracranial internal carotid artery, M1 and/or M2 segment) and extracranial severe internal carotid artery stenosis ≥90% (NASCET) or complete occlusion. Patients are randomized in two balanced parallel groups (1:1) to receive either intracranial mechanical thrombectomy plus internal carotid artery stenting (and at least one antiplatelet therapy) or intracranial mechanical thrombectomy alone within 8 h of stroke onset. Up to 432 patients are randomized after tandem occlusion confirmation on angiogram. Study outcomes: The primary outcome measure is complete reperfusion rate at the end of endovascular procedure, assessed as a modified Thrombolysis in Cerebral Infarction (mTICI) 3, and ≥4 point decrease in NIHSS at 24 h. Secondary outcomes include infarct growth, recurrent clinical ischemic event in the ipsilateral carotid territory, type and dose of antiplatelet therapy used, mRS at 90 (±15) days and 12 (±1) months. Safety outcomes are procedural complications, stent patency, intracerebral hemorrhage, and death. Economics analysis includes health-related quality of life, and costs utility comparison, especially with the need or not of endarterectomy. Discussion: TITAN is the first randomized trial directly comparing two types of treatment in patients with acute ischemic stroke due to anterior circulation tandem occlusion, and especially assessing the safety and efficacy of emergent internal carotid artery stenting associated with at least one antiplatelet therapy in the acute phase of stroke reperfusion. Trial registration: ClinicalTrials.gov NCT03978988